Trends in publication and collaboration of health-themed systematic reviews before and during the COVID-19 pandemic: A bibliometric study - Chiari, Williams; Amirah, Shakira; Lemu, Yohannes K.; Subbaram, Kannan; Edwards, Robert J.; Kretchy, James-Paul; Vento, Sandro; Khader, Yousef; Rademaker, Marius (Narra X, 2024)
The presence of global threats such as coronavirus disease 2019 (COVID-19) pandemic could potentially affect the research landscape, particularly that of systematic reviews. The aim of this study was to examine disparities between countries and the role of funding availability in the publication of health-themed systematic reviews. Metadata of published literature was collected from the Scopus database as of June 30, 2023. The dataset was divided into ‘pre-COVID-19 (2017–2019)’ and ‘during COVID-19 (2020–2022)’ by utilizing filter feature of the Scopus search engine. Network visualization of co-authorship was carried out on VoSviewer to identify collaborative patterns between countries. Our results suggest that most of the systematic reviews were published by authors from the United States of America (USA), both in pre-COVID-19 (n=29,463; Total link strength, TLS=32,832) and during COVID-19 (n=35,520; TLS=45,616). During COVID-19, the trend was not much different with the USA (14.6%), the UK (8.8%), and Australia (5%) in the top position among high-income countries. China (12.3%) and Iran (2.4%) topped the upper-middle-income and low-income countries groups. Publications by those who were from low-income countries were in a concerning low number; Ethiopia ranked first in this group only occupied 0.4% of the total publications (n=1,047). Furthermore, the number of publications was proportional to the number of funded studies (as observed in the top countries). However, during COVID-19 pandemic, the proportionality between funded publications and total publications was observed less. Taken altogether, our findings stress the importance of capacity building and providing more funds for on-desk research to close the disparity among countries.